"D" Is for Divorce: An Autoethnography. Issue 8 (16th November 2016) - Nicholas, Gianna
ABSTRACT: The purpose of this study is to critically examine the author's adult experience of her parents' divorce. Through the use of reflexive authoethnography, she details the event of the divorce and the feelings and emotions experience as an adult, only child. Furthermore, she offers her inner thoughts and observations on how to comprehend and live through an unexpected change. Findings may assist others affected by divorce, experiencing grief, or learning to cope with life-altering events.